Indonesian EFL teachers’ cognitions and practices related to social justice - Sulistyowardani, Margaretha; Mambu, Joseph Ernest; Pattiwael, Athriyana Santye (Indonesian Journal of Applied Linguistics, 2020)
The implementation of critical pedagogy has not been well addressed, especially that viewed from the teacher cognition perspective. This project hence aims to study the cognitions and practices related to critical pedagogy by investigating the integration of social justice by high-school English teachers in Indonesia. Two participants who claimed to be critical pedagogy practitioners were interviewed and observed. Interviews were done before and after the class observation. Pre-observation interviews were done in order to identify teachers’ cognition and track factors contributing to the integration of social justice in the ELT classroom. Meanwhile, the post-observation interviews were performed to seek for clarification in relation to the congruence and incongruence between the cognitions and the real practices. Participants’ schooling experience, curriculum demand, and personal beliefs seem to play a major role in the integration of social justice in class. However, incongruence was also recognized between their stated cognition and real practices.